Financial Crisis Management and Democracy Lessons from Europe and Latin America - De Souza Guilherme, Bettina; Ghymers, Christian; Griffith-Jones, Stephany; Ribeiro Hoffmann, Andrea (Springer International Publishing : Imprint: Springer, 2021)
This open access book discusses financial crisis management and policy in Europe and Latin America, with a special focus on equity and democracy. Based on a three-year research project by the Jean Monnet Network, this volume takes an interdisciplinary, comparative approach, analyzing both the role and impact of the EU and regional organizations in Latin America on crisis management as well as the consequences of crisis on the process of European integration and on Latin America's regionalism. The book begins with a theoretical introduction, exploring the effects of the paradigm change on economic policies in Europe and in Latin America and analyzing key systemic aspects of the unsustainability of the present economic system explaining the global crises and their interconnections. The following chapters are divided into sections. The second section explores aspects of regional governance and how the economic and financial crises were managed on a macro level in Europe and Latin America. The third and fourth sections use case studies to drill down to the impact of the crises at the national and regional levels, including the emergence of political polarization and rise in populism in both areas. The last section presents proposals for reform, including the transition from finance capitalism to a sustainable real capitalism in both regions and at the inter-regional level of EU-LAC relations.The volume concludes with an epilogue on financial crises, regionalism, and domestic adjustment by Loukas Tsoukalis, President of the Hellenic Foundation for European and Foreign Policy (ELIAMEP). Written by an international network of academics, practitioners and policy advisors, this volume will be of interest to researchers and students interested in macroeconomics, comparative regionalism, democracy, and financial crisis management as well as politicians, policy advisors, and members of national and regional organizations in the EU and Latin America. .